2017
DOI: 10.3390/rs9090925
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Variability and Oceanographic Dynamics of the Central and Southern Coastal Zone of Sonora in the Gulf of California

Abstract: This study analyzed monthly and inter-annual variability of mesoscale phenomena, including the El Niño Southern Oscillation (ENSO), the Pacific Decadal Oscillation (PDO) climate indexes and wind intensity considering their influence on sea surface temperature (SST) and chlorophyll a (Chl-a). These analyses were performed to determine the effects, if any, of climate indexes and oceanographic and environmental variability on the central and southern coastal ecosystem of Sonora in the Gulf of California (GC). Mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
27
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 63 publications
8
27
0
2
Order By: Relevance
“…They found winter conditions from December to April and summer conditions from June to October, with an increase of SST from 16 • in February-March to 31 • C in August. The SST values were similar to Valenzuela-Sánchez [23], Soto-Mardones et al [22] and García-Morales et al [29], as well as in this study. Bernal et al [50] report that the variability in this region is caused by the effects of seasonal winds and the oceanographic influence from the Pacific Ocean, the seasonal coastal winds develop a sea surface circulation along the Eastern Coast, to the south during October-March and to the north during June-September [8].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…They found winter conditions from December to April and summer conditions from June to October, with an increase of SST from 16 • in February-March to 31 • C in August. The SST values were similar to Valenzuela-Sánchez [23], Soto-Mardones et al [22] and García-Morales et al [29], as well as in this study. Bernal et al [50] report that the variability in this region is caused by the effects of seasonal winds and the oceanographic influence from the Pacific Ocean, the seasonal coastal winds develop a sea surface circulation along the Eastern Coast, to the south during October-March and to the north during June-September [8].…”
Section: Discussionsupporting
confidence: 92%
“…This gradient from south to north is similar to the results for whole Gulf of California described by Soto-Mardones et al [22], Escalante et al [24] and Hidalgo-González and Álvarez-Borrego [43]. This SST distribution, during the warm period, can be explained by the fact that the direct communication with the Tropical Pacific Ocean allows the entry of Equatorial Surface Water [29,44], and inside the Gulf of California it is modified by greater solar irradiance and evaporation effects [42], generating this gradient. During the cold period, SST decrease inside the Gulf by physical dynamics such tidal and wins mixing [25], mainly in the Midriff Islands and North Regions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A number of important fisheries declined during ocean warming associated with the strong El Niño events of 1982-1983 and 1997-1998, but recovery was observed in both cases during subsequent La Niña conditions as cool, productive water returned to the region (Bakun et al, 2010;Lluch-Cota et al, 2010). However, alongside the return of El Niño conditions in 2009-2010 and 2015-2016, persistent ocean warming (Hoving et al, 2013;Frawley, 2019) has been observed across the central Gulf of California alongside decreasing upwelling and primary productivity (as inferred by chlorophyll a) along the eastern coast (Robinson et al, 2016;García-Morales et al, 2017). Though research results remain disaggregated, observations concerning changes in the distribution and abundance of marine mammals (Elorriaga-Verplancken et al, 2016), seabirds , sea turtles (Zavala-Norzagaray et al, 2017), and other marine taxa (Hoving et al, 2013;Fernández-Rivera Melo et al, 2018) suggest that the impacts on marine animals have been significant.…”
Section: Recent Oceanographic and Ecological Trendsmentioning
confidence: 98%
“…SST variability due to ENSO has been shown to globally impact on ecosystem structures on various spatial scales. This includes the oceans surrounding Australia (Pearce and Feng, 2013;Sprogis et al, 2017;Arias-Ortiz et al, 2018;Benthuysen et al, 2018;Stuart-Smith et al, 2018), the Peruvian Upwelling Ecosystem (Quispe-Ccalluari et al, 2018), the Gulf of California (García-Morales et al, 2017) and the northeastern Arabian Sea (Vidya and Kurian, 2018).…”
Section: Introductionmentioning
confidence: 99%